2022
DOI: 10.1177/03611981221123801
|View full text |Cite
|
Sign up to set email alerts
|

Strangers On This Road We Are On: A Literature Review of Pooling in On-Demand Mobility Services

Abstract: Ridepooling service options introduced by transportation network companies (TNCs) and microtransit companies provide opportunities to increase shared-ride trips in vehicles, thereby improving congestion and environmental factors. This paper reviews the existing literature available on ridepooling and related services, specifically focusing on pooling options available from on-demand transportation companies. The paper summarizes the existing knowledge on the use of pooled-ride services, factors in travel mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…On-demand transportation services allow passengers to book rides, usually through a digital application or platform, at locations and times convenient to them, as opposed to services that only travel between specific locations or follow a strict schedule, such as fixed-route public transit. Some examples include TNCs that connect travelers to drivers using personal vehicles, which can also be provided as a shared service with other unknown passengers as well as microtransit services, which pool passenger trips in shuttles or vans together using real-time routing and scheduling (Hansen and Sener 2022).…”
Section: Questionsmentioning
confidence: 99%
“…On-demand transportation services allow passengers to book rides, usually through a digital application or platform, at locations and times convenient to them, as opposed to services that only travel between specific locations or follow a strict schedule, such as fixed-route public transit. Some examples include TNCs that connect travelers to drivers using personal vehicles, which can also be provided as a shared service with other unknown passengers as well as microtransit services, which pool passenger trips in shuttles or vans together using real-time routing and scheduling (Hansen and Sener 2022).…”
Section: Questionsmentioning
confidence: 99%
“…The report by Hansen & Sener indicated that ridesharing is more likely to be considered by lower incomes public transit users [30]. Hence, time and cost are two important factors for users to determine whether to choose the ridesharing mode.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ride-pooling services have gained popularity as a ride-sourcing transportation option, as they allow more than one passenger's request to be served in one ride, thus reducing the number of vehicles on the network [1]. Transportation Network Companies (TNCs) view ride-pooling services as a way to increase ridership, reduce customer cost, and expand ridesharing options [2]. Uber and Lyft, the two most popular ride-hailing companies, offer Uber Pool and Lyft Line Future Transp.…”
Section: Introductionmentioning
confidence: 99%
“…As part of an Uber Pool trip, Uber determines the best route along which multiple riders are going to be picked up [4]. In addition to offering rides at a reduced cost to customers, ride-pooling is viewed by many as a great way to reduce urban traffic congestion [1,2,5]. However, there is still a lack of clarity regarding the true impact of ride-pooling services on traffic network operations, in general, and traffic congestion in particular, due to the limited amount of research conducted on those topics.…”
Section: Introductionmentioning
confidence: 99%